INDENTIFIKASI DAN ANALISIS DERAJAT ULKUS KAKI DIABETIK - Aristiyani, Desty; Hasneli, Yesi; Woferst, Rismadefi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Diabetes mellitus is a chronic desease which is identified by hyperglycemia condition and may increase the risk of microvascular and macrovascular complications due to neuropathy. The purpose of this research was to identify and analyze the grade of diabetic foot ulcer based on Meggitt-Wagner system towards the diabetes mellitus sufferers who got diabetic foot ulcer in hospitalization in RSUD Arifin Achmad hospital. The methode of this research was observational analitic with cross sectional design. The samples was taken by total sampling. This study observed a number of 37 diabetic patient in hospitalization with diabetic foot ulcer. There were 37 patient in hospitalization with diabetic foot ulcer in RSUD Arifin Achmad hospital on July 2018. Observation was to identifiy dan analyze grade of diabetic foot ulcer based on characteristic of Meggitt-Wagner system. The result showed majority characteristics of respondents of diabetic foot ulcer were female 26 (70,3%), 56-65 yeras old 17 (45,9%), and duration of history of diabetic less than 5 years 15 (40,5%). The Result of identification and analysis grade of diabetic foot ulcer showed that majority were in the grade 1 with superficial wounds characteristic. Recommended for patients to controll blood glucose and treat wounds and feet to preventing advanced complications. Keyword : Diabetic foot, diabetes mellitus, Meggitt-Wagnerâs grade , Meggitt-Wagner grade